2007
DOI: 10.1111/j.1471-6402.2007.00370.x
|View full text |Cite
|
Sign up to set email alerts
|

Voice Matters: Buffering the Impact of a Negative Climate for Women in Science

Abstract: The current study examined whether women scientists' perceptions of voice moderate the impact of poor workplace climates on job satisfaction and whether effective leadership and mentoring promote women's voice. Survey data were collected from 135 faculty women in the natural sciences. The results from multiple regression analyses indicated that negative (e.g., sexist, hostile) departmental climates were related to lower job satisfaction. However, voice interacted with climate, such that women who perceived tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(72 citation statements)
references
References 77 publications
2
67
0
Order By: Relevance
“…Previous research in the United States suggests that workplace climates that are sexist toward women are related to lower job satisfaction for female employees (Mansfield et al 1991;Settles et al 2006Settles et al , 2007Willness et al 2007). The relationship between these climates and the satisfaction of male employees, however, is still in dispute (Barak et al 1998;Kossek and Zonia 1993;Miner-Rubino and Cortina 2007;Settles et al 2007).…”
Section: Introductionmentioning
confidence: 89%
“…Previous research in the United States suggests that workplace climates that are sexist toward women are related to lower job satisfaction for female employees (Mansfield et al 1991;Settles et al 2006Settles et al , 2007Willness et al 2007). The relationship between these climates and the satisfaction of male employees, however, is still in dispute (Barak et al 1998;Kossek and Zonia 1993;Miner-Rubino and Cortina 2007;Settles et al 2007).…”
Section: Introductionmentioning
confidence: 89%
“…Ragins and Cotton ( 1999 ) found that female mentees with female mentors were more likely to engage in social activities with their mentors than mentees in any other demographic composition. Settles et al ( 2007 ) found that mentoring by other women, but not by men, enhanced a sense of voice for female scientists. These psychosocial benefi ts of same-sex mentoring are important for employee well-being, and they may be diffi cult to achieve in cross-sex mentoring relationships where intimacy is hindered by concerns of sexual innuendo .…”
Section: Will You Mentor Me?mentioning
confidence: 96%
“…Still, some evidence points to an inverse relationship between women's minority size and academic success, noting that a larger proportion of women does not necessarily reduce the negative treatment of women or negative perceptions of gender-attributes and science (Acker 1990;Settles et al 2007;Toren and Kraus 1987). It remains possible that as women increase their representation in a field or a department they create a separate class Women in STEM networks 771 of researchers that rely on one another, remaining isolated from the majority population of men scientists (Kanter 1977;South et al 1982).…”
Section: Field Of Sciencementioning
confidence: 97%
“…Because networks and socialization are critical to the training and professional development of scientists, they become even more important for women scientists who are in the minority in most fields of science. Researchers argue that less visible social cues, negative interactions, and lack of access to important networks create structural impediments to women's careers and accumulate over the course of women's careers (Merton 1973;Settles et al 2007;Zuckerman 1989) resulting in frustration and withdrawal.…”
Section: Network In Sciencementioning
confidence: 98%